If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -7) * 3 = 10x + -9 Reorder the terms: (-7 + 2x) * 3 = 10x + -9 Reorder the terms for easier multiplication: 3(-7 + 2x) = 10x + -9 (-7 * 3 + 2x * 3) = 10x + -9 (-21 + 6x) = 10x + -9 Reorder the terms: -21 + 6x = -9 + 10x Solving -21 + 6x = -9 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -21 + 6x + -10x = -9 + 10x + -10x Combine like terms: 6x + -10x = -4x -21 + -4x = -9 + 10x + -10x Combine like terms: 10x + -10x = 0 -21 + -4x = -9 + 0 -21 + -4x = -9 Add '21' to each side of the equation. -21 + 21 + -4x = -9 + 21 Combine like terms: -21 + 21 = 0 0 + -4x = -9 + 21 -4x = -9 + 21 Combine like terms: -9 + 21 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| -43=x/16 | | x-1=6/x | | 6x^3+56=53x-x^2 | | 7=5/6b-8 | | Y^2+3y=x | | (6+4x)*(15x+25)=0 | | F(x)=4*logx | | 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 | | 4(2b-5)=2b+10 | | X/5-7=2 | | 2.3=y+.9 | | 12c-48=84 | | 9x-5=3x+47 | | x(x+13)=40 | | (1+2i)*x+(3-5i)*y=1-3i | | -3=2-(-x/5) | | 14x^2-5x+1=0 | | -12+x=60 | | 7x^2-14x-5=0 | | -6/13f=-48 | | 2nw=a | | xy-bx-ay+ab=0 | | 7/x=35/15 | | 2/3=5/2g | | x/12=12/72 | | -5/7d=15/14 | | y=4(27)+3 | | -7y+3=38 | | a+57=-60 | | -9h-6+12h=22 |